Adalimumab-induced sensory vasculitic neuropathy. Issue 1 (17th January 2022) - Sim, Nicholas Keyi; Ismail, Azzam; Alam, Taimour; Shanmugarajah, Priya Devi
Abstract : Vasculitis and other autoimmune conditions are known complications of tumour necrosis factor alpha (TNF-α) inhibitor use. By definition, TNF-α inhibitor induced vasculitis is a secondary systemic vasculitis. However, its phenotype is varied and can present as an isolated vasculitic neuropathy. This presents a diagnostic challenge as the gold standard for diagnosis of a vasculitic neuropathy is a peripheral nerve biopsy that meets predefined histopathological criteria. Given the poor sensitivity of the peripheral nerve biopsy, it is important that clinicians take a good history and maintain a high index of suspicion, as this is a treatable iatrogenic condition. Here we present a case of adalimumab-induced sensory vasculitic neuropathy, treated according to the Peripheral Nerve Society guideline for non-systemic vasculitic neuropathy, given her disease phenotype.